MODEL EVALUASI SELF ASSESSMENT DAN PEER ASSESSMENT UNTUK MENINGKATKAN HASIL BELAJAR MATERI AKHLAK MULIA DI SMAN 2 SUMBAWA BESAR - Hendra Julianto; Lely Wahyu Ningrat; Yanda Amalia; Fandi Yuspika Irawan; Nurfina; Romelah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of self-assessment and peer assessment evaluation models in an effort to improve learning outcomes and their impact on students regarding the subject matter of Noble Character (Akhlak Mulia) at SMAN 2 Sumbawa Besar. This study employs a qualitative approach with a case study research design, conducted at SMAN 2 Sumbawa Besar. The research informants consisted of a PAI (Islamic Religious Education) teacher with the initials NH, and four students comprising two male students with the initials B1 and B2, as well as two female students with the initials C1 and C2, all from class XI.13. Data collection techniques included observation, interviews, and documentation. Data analysis followed the theory of Miles, Huberman, and Saldana, with the following steps: data collection, data condensation, data presentation, and conclusion drawing. Data validity testing was conducted using source triangulation. The findings indicate that the implementation of self-assessment and peer assessment-based evaluation models consistently promotes improvements in students' self-awareness, motivation, and internalization of noble character values. The reflective process facilitated by these instruments has been shown to strengthen a holistic understanding of noble character encompassing the cognitive, affective, and psychomotor domains. This study discusses the importance of integrating Wiggins-based authentic evaluation models into Islamic Religious Education (PAI) learning at the senior high school level.